Localization of Actin mRNA during the Establishment of Cell Polarity and Early Cell Divisions in Fucus Embryos. - Bouget, F. Y. (1996)
Localization of mRNA is a well-described mechanism to account for the asymmetric distribution of proteins in polarized somatic cells and embryos of animals. In zygotes of the brown alga Fucus, F-actin is localized at the site of polar growth and accumulates at the cell plates of the first two divisions of the embryo. We used a nonradioactive, whole-mount in situ hybridization protocol to show the pattern of actin mRNA localization. Until the first cell division, the pattern of actin mRNA localization is identical to that of total poly(A)+ RNA, that is, a symmetrical distribution in the zygote followed by an actin-dependent accumulation at the thallus pole at the time of polar axis fixation. At the end of the first division, actin mRNA specifically is redistributed from the thallus pole to the cell plates of the first two divisions in the rhizoid. This specific pattern of localization in the zygote and embryo involves the redistribution of previously synthesized actin mRNA. The initial asymmetry of actin mRNA at the thallus pole of the zygote requires polar axis fixation and microfilaments but not microtubules, cell division, or polar growth. However, redistribution of actin mRNA from the thallus pole to the first cell plate is insensitive to cytoskeletal inhibitors but is dependent on cell plate formation. The F-actin that accumulates at the rhizoid tip is not accompanied by the localization of actin mRNA. However, maintenance of an accumulation of actin protein at the cell plates of the rhizoid could be explained, at least partially, by a mechanism involving localization of actin mRNA at these sites. The pattern and requirements for actin mRNA localization in the Fucus embryo may be relevant to polarization of the embryo and asymmetric cell divisions in higher plants as well as in other tip-growing plant cells.